Biotransformation of ginsenosides by glycoside hydrolase from an endophytic fungus of Panax ginseng - Linggai Cao; Shizhou Yu; Lanlan Zhang; Xiaolian Zhang; Yuhua Li (Biotechnology & Biotechnological Equipment)
Endophytes, symbiotically with their host plants, are frequently found in the roots of Panax ginseng. To explore ginsenosides biotransformation by endophytic fungi, 26 such fungi were isolated from ginseng roots sourced from four distinct planting regions, and their glycosyl hydrolysis activities were measured. Of these endophytic, 20 isolates exhibited glycosidase enzymes capable of cleaving glycosidic bonds of glucose, arabinofuranose and arabinopyranose. Notably, the glycosidase BglNh gene was isolated and cloned from Nectria haematococca, one of the endophytic fungi. Enzymatic assessments unveiled that BglNh specifically catalyzes the hydrolysis of glucose residues located external to the C-3 position of protopanaxadiol ginsenosides under optimal reaction conditions (pH 6.0 and temperature 35 °C). Our findings demonstrate the efficient conversion of major ginsenosides Rb1, Rb2 and Rc to minor ginsenosides Gyp17, CO and CMc1, highlighting the potential of these fungi for ginsenoside biotransformation and bioactive compound production.